Two-Step Solvothermal Synthesis of (Zn(0.5)Co(0.5)Fe(2)O(4)/Mn(0.5)Ni(0.5)Fe(2)O(4))@C-MWCNTs Hybrid with Enhanced Low Frequency Microwave Absorbing Performance - Yin, Pengfei (Nanomaterials (Basel), 2019)
In this study, the quaternary hybrid of (Zn(0.5)Co(0.5)Fe(2)O(4)/Mn(0.5)Ni(0.5)Fe(2)O(4))@C-MWCNTs with high-performance in low frequency electromagnetic absorption was synthesized via a facile two-step solvothermal synthesis method. The physicochemical properties as well as electromagnetic parameters and microwave absorption performance were characterized by XRD, SEM, TEM, RS, TGA, and VNA, respectively. The results indicate a nuclear-shell morphology of this hybrid for amorphous carbon coated on the surface of Zn(0.5)Co(0.5)Fe(2)O(4) and Mn(0.5)Ni(0.5)Fe(2)O(4) mixed polycrystalline ferrites. In addition, the MWCNTs synchronously enwind in the nuclear-shell NPs to form a special cross-linking structure. The outstanding low frequency microwave absorption property is attributed to the synergistic effect of dielectric and magnetic loss, better impedance matching condition, and excellent attenuation characteristics of the as-prepared paramagnetic quaternary hybrid. Maximum RL of −35.14 dB at 0.56 GHz with an effective absorption bandwidth in the range of 0.27–1.01 GHz can be obtained with thickness of 5 mm. This hybrid exhibits superior low frequency microwave absorption properties compared with other ferrite-carbon nanocomposites. This investigation provides a new route to prepare suitable candidates for the absorption of electromagnetic waves in a low frequency band on account of its good performance and simple preparation process.